Clinicopathological characteristics of hepatitis B surface antigen-negative and hepatitis C antibody-negative hepatocellular carcinoma - IIDA, HIROYA (Oncol Lett, 2015)
The present study investigated the clinicopathological characteristics of resected hepatitis B virus surface antigen (HBs-Ag)-negative, hepatitis C virus antibody (HCV-Ab)-negative hepatocellular carcinoma (NBNC HCC). The clinicopathological characteristics of 164 patients with NBNC HCC, 144 patients with HBs-Ag-positive HCC (HBV group) and 550 patients with HCV-Ab-positive HCC (HCV group) were compared. In the NBCN HCC group, 61 patients succumbed after 2 years. Subsequently, NBCN HCC patients were compared according to survival time (<2 years, 39 patients vs. ≥2 years, 64 patients) to identify prognostic factors. Finally, the clinicopathological characteristics of NBNC HCC were compared according to history of alcohol abuse/pathological results: Non-alcoholic steatohepatitis HCC (NASH group, 40 patients), alcohol abuse HCC (AL group, 80 patients) and other HCCs (non-NASH/non-AL group, 44 patients). Age, diabetes prevalence and body mass index were significantly higher for NBNC HCC compared with virus-related HCC. Among stage II cases, the prognosis was significantly better for the NBNC compared with that for the HCV group. A high α-fetoprotein level, poorly differentiated HCC and advanced liver fibrosis were independent risk factors for the prognosis of NBNC HCC. The proportion of female patients was significantly higher among NASH compared with AL HCC patients. The cumulative survival rates following surgery were similar in the NASH, AL and non-NASH/non-AL groups. NBNC HCC is considered to be a lifestyle disease, with better prognosis for stage II patients. The prognostic factors for NBNC HCC patients undergoing hepatectomy were similar to those with virus-related HCC and did not differ according to alcohol abuse history or pathological results.